Evaluasi peran aparat pengawas intern pemerintah dalam manajemen risiko - Carolina, Yohana; Tobing, Agustinus Lumban (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
The embodiment of an effective APIP role is to provide early warning and increase the effectiveness of risk management in carrying out the duties and functions of government agencies according to the mandate in Government Regulation Number 60 of 2008 concerning the Government Internal Control System (SPIP). In realizing this role, APIP encourages an increase in the level of SPIP maturity and the level of APIP capability assessment through the establishment of risk management policies and internal audit activities. However, the implementation of risk management has not had an optimal impact in anticipating organizational problems in achieving its goals with findings of weaknesses in SPIP and the role of APIP which have not added value to improving organizational control. The evaluation is carried out to provide improvements to APIP's role in risk management in accordance with the principles of the COSO Internal Control Framework (ICF). The research method was carried out in a qualitative descriptive and comparative analysis using a case study approach. The results of the study found weaknesses in that risk management practices were only in the implementation stage and had not yet become a culture within the organization, lack of HR competency related to risk management, and risk management processes had been documented but had not been integrated with business processes and had not been carried out on time. Internal audit activity is not yet optimal in guaranteeing the quality of risk management. It is hoped that the research results will improve APIP's role in the risk management process through guidelines, internal audit activities, and appropriate audit procedures.